Penerapan Metode RAD dalam Sistem Ujian Penerimaan Mahasiswa Baru di Universitas Catur Insan Cendekia - Lutfi, Muhammad; Asfi, Marsani; Sevtiana, Agus (LPPM UNIKA Santo Thomas Medan, 2023)
The university and college student admission process includes various selection methodslike written and psychological exams. Not all institutions rely on exams; some use academic achievements, such as certificates or awards, like Catur Insan Cendekia University. Currently, there's no online exam application for new student registration. The development of a web-based interactive application aims to simplify registration for prospective Catur Insan Cendekia University students. It employs Potential Test Academics and Academic Aptitude Tests to assist in entrance selection. This application is expected to greatly aid in the new student admissions process. Implementing the RAD system in new student admission has successfully created a tool to conduct exams for prospective students. Embracing technology in online exams has increased, leveraging automation and efficiency. Technological advancements have notably reduced manual workloads, expediting processes and enhancing the online exam system.